THERMAL ANALYSIS OF A OF BRAKE DISC ROTOR FOR PERSONAL ELECTRIC VEHICLE - Hassan, Muhammad Zahir; Abdul Munir, Fudhail; Mohamad Zin, Mohd Rody; Mohd Irwan, Mohd Azmi (2012)
In this paper, thermal analysis of a brake disc rotor design for a personal electric vehicle(PEV) is demonstrated. The finite element method was used to obtain the temperature behavior during braking and non-braking conditions. Steady state response in temperature distributions was conducted for this research paper. The analysis is limited to heating and cooling condition of the designed brake disc rotor.